Diaphragmatic breathing as treatment for escape‐maintained aggression. (8th March 2019) - Phillips, Lauren A.; Fritz, Jennifer N.; Rettig, Lisa A.; Martin, Kaitlyn E.
Abstract : Coping skills, such as diaphragmatic breathing, are commonly recommended to help individuals work through challenging situations. We evaluated diaphragmatic breathing as treatment for aggression of three individuals diagnosed with autism spectrum disorder or Angelman syndrome. Functional analysis results demonstrated that each participant engaged in aggression maintained by social‐negative reinforcement. Diaphragmatic breathing treatment without extinction was conducted in a work context and involved prompting diaphragmatic breathing contingent on precursors to aggression; treatment was effective in reducing the rate of aggression for one of three participants. For the two other participants, other reinforcement‐based interventions (differential reinforcement of other behavior or functional communication training with extinction) were necessary to decrease aggression.